Book review: Marcum, Denna and Schonfeld, Roger C. Along came Google: A history of library digitization - Elena Maceviciute (Information Research: An International Electronic Journal)
Marcum, Denna and Schonfeld, Roger C. Along came Google: A history of library digitization. Princeton: Princeton University Press, 2023. x, 222 p. ISBN 978-0-691-22437-4